ACCOUNT LOG IN: THE ONLINE MODULAR INSTRUCTIONS OF THE LEARNING ENVIRONMENT NETWORK SYSTEM (LENS) - AGUSTIN, CHONA (International Journal of Arts, Sciences and Education, 2021)
ABSTRACT: The generation of youth (Net Generation) which is growing up with modern information and communication technologies strongly shaping their mental models, is interested in keeping up with the rapidly changing technological world. Education must adapt its teaching and learning approaches to be consistent with the ever-changing social world. Educational institutions must make use of the new systems available to promote greater interaction and collaborative learning. The Internet is not just a form of entertainment. It is also a valuable teaching tool. Online courses and degree program offerings are advancing to develop in the modern age. Various professors are deeply emerged in the development and transforming of conventional courses into an online format. The kind of class as well as the teacher can also affect a students’ online involvement, and instructor training for online courses is vital. When organizing online courses, student input involving experience and expectations is of great significance. Forecasting models of online student effort, performance and success have been important areas of study. Exploring to address competence and the expectations of prospective online learners and to employ strategies to best meet the demands of the online learner has been the motivation of this undertaking. The purpose of this study, therefore, was to determine the perceptual experiences of GEC 109 class on online modular instruction of the Learning Environment Network System. The participants for this study consisted of students enrolled in GEC 109-Understanding the Self. A modified survey instrument was developed by the researcher that was patterned from the survey instrument used by the University in the beginning of the pandemic. The descriptive-quantitative method of research was used in this study. The student-participants who were enrolled in the course were asked to complete an online survey regarding their experiences of online modular instruction of the Learning Environment Network System. The data gathered in this study were presented, interpreted, and analyzed using the frequencies and percentages to provide a clear demographic profile of the participant-respondents and their experiences on online modular instruction of the Learning Environment Network System. The findings of this study revealed that the conduct of the modular instruction of the course through online activities has been adopted positively by the students, though their effective engagement with the different class activities has been hampered by their poor internet connectivity thus limits their efficient engagement with the course. As revealed in the findings of this study, the following recommendations for additional research are offered, to wit, since online courses will be part of many higher educations’ offerings, it is important to monitor students’ engagements and devise ways for an effective and interactive students’ engagement, internet connectivity should be improved to allow the students to a full interactive and efficient class engagement while developing successful and dynamic teaching methods, technological inadequacies of students and teachers should be addressed and most importantly, the institution as the primary source of the program system should design a strategy to better provide an uninterrupted service especially during class sessions and examinations.